Working visits to MARDI, Nasuha Herb Farm and Bogor Agricultural Institute - Asdarina, Yahya (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP)'s land application submitted to the Pahang state government through the State Economic Planning Unit (EPU) in 2011 was approved and following that, a series of visits were planned and carried out by the Research and Innovation Department (JP&I) with the cooperation from the Property Development and Management Department and Vice Chancellor Office.